Development of a high performance liquid chromatography-based toxicological screening procedure for neutral and acidic drugs in the urine of posoned patients - du Plessis, Jan Bastiaan (Bloemfontein: Central University of Technology, Free State, 1994)
The necessity of developing broadly based in-house toxicology screening procedures and their associated databases in any department purporting to offer a toxicology service, cannot be overestimated. The development, in the past twenty years, of a number of different immunoassay techniques with which a large number of target compounds can be detected very selectively, all too often lulls the physician treating a drug overdose case into a false sense of security once a specific compound has been identified This is so because, once a drug has been identified which appears to account for the patient's condition, the search for other possible contributors is more often than not, abandoned. The aim of this study was to develop a screening procedure for neutral and acidic drugs in the urine of poisoned patients to complement the already existing gas chromatographic screening procedure for basic drugs. Sixty different substances were identified as a nucleus with which to launch the project. These substances were selected on the basis of their availability to the public and on data of overdose cases treated in this laboratory during the past twenty three years. Information on a large number of published screemng procedures for these type of compounds and the various techniques involved in their isolation, detection and identification, was collected initially. These techniques were subsequently- optimised with the aim to develop a combined high performance liquid chromatography / diode array detector / UV spectral database based screening procedure which is simple and can be performed rapidly at reasonable costs. The liquid-liquid extraction procedure for acidic and neutral drugs, with diethyl ether as organic solvent and a clean-up washing step with lead acetate solution, gave good recoveries and yielded chromatograms with little interference by endogenous compounds. The general applicability of this screening procedure in a senes of suspected drug • overdoses, has lead to the isolation and identification of a number of drugs added as standards to the spectral database as well as some unexpected compounds which were subsequently added to the database. Metabolites of several drugs were also identified in the urine of patients in some of the case reports presented. The data on these compounds were likewise added and are still being added to the spectral library whenever new data become available during the treatment of overdose cases. The metabolite patterns of drugs obtained in this way are invaluable additions to the screening procedure as they contribute significantly to making the identification of isolated drugs unambiguous. The simplicity and speed of the developed screemng procedure, makes it ideal for toxicological screening since the whole procedure can be performed in under an hour. Because a simple liquid-liquid extraction procedure is used, the costs are less than normally encountered with solid phase extraction methods. Moreover, it is certainly much cheaper and faster than a series of immunoassay-based target analyses which would be needed to cover even a small fraction of the compounds which can be isolated and identified by this broadly based procedure. The results obtained in this study demonstrated that selective testing could have grave consequences for the patient. Commercially available quick tests for toxicology screening can be misleading because clinicians can get a false impression of the abilities oflaboratories rendering such services. This was illustrated in a number of case studies by using the screening procedure developed during this study. A good example is the case in which theophylline was found during an HPLC screening. On the basis of the patient's history the clinicians only requested target analyses for anticonvulsants of which two were actually found in the patient's plasma and of which one was at a concentration which could account for the patient's clinical condition. The high plasma level of theophylline assayed subsequent to theophylline being detected in the stomach content, could have been fatal. It can be concluded that this project yielded a comprehensive and versatile screening method and database for the identification of acidic and neutral drugs in urine. The data obtained during several of the case studies contributed information which was useful in the treatment of the patients involved
Thesis
Keywords: Poisoning - Diagnosis; Urine - Analysis; High performance liquid chromatography - Methodology; Toxicology - Research